ANALYSIS OF LONG-TERM RESULTS OF MEDICAL AND SURGICAL TREATMENT OF PATIENTS WITH SEVERE CHRONIC HEART FAILURE - O. T. Kotsoeva; O. L. Boсkeriya (Klinicist)
Objective: study was analysis of long-term results of medical and surgical treatment of patients with severe chronic heart failure (CHF).Materials and methods. We studied 90 patients with CHF III–IV functional class (FC) of NYHA, treated in A.N. Bakulev Scientific Center for Cardiovascular Surgery in 2007. All patients were divided into 3 groups: 30 patients who underwent conventional medical therapy (MT); 30 patients who underwent cardiac resynchronization therapy (CRT); 30 patients extremely severe category, which was performed orthotopic heart transplantation. Patients were followed up for 5 years to assess long-term results of treatment of CHF.Results. In patients with severe CHF, CRT (with respect to MT) significantly reduces the 5-year risk of total mortality, death from progressive heart failure, rehospitalization for heart failure, cardiac arrhythmias, need for heart transplantation, as well as helping to reduce FC of CHF, and an increase in ejection fraction the left ventricle.Conclusion. Surgical treatment of patients with severe CHF demonstrated a significant advantage over conventional MT in terms of improving the 5-year forecast.